2023
DOI: 10.1142/s0219265922500062
|View full text |Cite
|
Sign up to set email alerts
|

Proper (Strong) Rainbow Connection and Proper (Strong) Rainbow Vertex Connection of Some Special Graphs

Abstract: The proper rainbow vertex connection number of [Formula: see text], denoted by [Formula: see text], is the smallest number of colors needed to properly color the vertices of [Formula: see text] so that [Formula: see text] is rainbow vertex connected. The proper strong rainbow vertex connection number of [Formula: see text], denoted by [Formula: see text], is the smallest number of colors needed to properly color the vertices of [Formula: see text] so that [Formula: see text] is strong rainbow vertex connected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This concept has undergone significant development. Many researchers apply it to various classes of graphs, such as pencil graphs [12], connected graphs [13], star fan graphs [14], and some special graphs [15]. Chen et al [16,17] provided the rainbow vertex connection of a graph and its complexity and showed that it was an NP-hard problem.…”
Section: -Introductionmentioning
confidence: 99%
“…This concept has undergone significant development. Many researchers apply it to various classes of graphs, such as pencil graphs [12], connected graphs [13], star fan graphs [14], and some special graphs [15]. Chen et al [16,17] provided the rainbow vertex connection of a graph and its complexity and showed that it was an NP-hard problem.…”
Section: -Introductionmentioning
confidence: 99%